Mechanism of soil microbial community degradation under long-term tomato monoculture in greenhouse - Li, Menglu; Chen, Xiaobo; Cui, Yushuang; Yue, Xin; Qi, Lianfen; Huang, Yali; Zhu, Changxiong (Frontiers in Microbiology, 2025)
Tomato (Solanum lycopersicum L.), an economically significant crop, is frequently cultivated in greenhouses under continuous monoculture systems. Motivated by intensive agricultural practices and economic incentives, continuous cropping has become prevalent in China, yet it often results in soil degradation, including nutrient imbalances and microbial community shifts. However, the mechanisms driving soil deterioration in prolonged greenhouse monoculture remain unclear. In this study, soil samples from greenhouses with varying durations of continuous tomato cropping (1–3 years, 5–7 years, and >10 years) were analyzed for microbial and chemical parameters using 16S rRNA and ITS sequencing and soil nutrient assays. Results demonstrated a significant increase in fungal abundance and diversity in >10 years samples, alongside reduced bacterial richness. Co-occurrence network analysis revealed opposing trends in bacterial and fungal networks, indicating a shift from bacterial to fungal dominance. This shift correlated with impaired microbial functions, including diminished metabolic activity and impaired carbon-nitrogen cycling. PLS-PM model identified the accumulation of soil organic matter (SOM), nitrogen (N), and phosphorus (P) as key drivers of microbial community restructuring. Functional gene predictions based on 16S rRNA sequencing indicated that the expression of genes related to carbon (tktA/tktB, accA, acsB, cooS/acsA, ppc) and nitrogen (pmoA-amoA, nxrA, hao, nasA, nasB, gdh, ureC, narG, nirB, nirK, norB, nosZ) transformation were decreased. Mantel test further highlighted KD4_96 and Bacillus as critical regulators of carbon and nitrogen dynamics. These findings elucidate mechanisms underlying soil degradation in long-term greenhouse monoculture systems and provide a theoretical basis for sustainable soil management strategies.